Localized Wounding by Heat Initiates the Accumulation of Proteinase Inhibitor II in Abscisic Acid-Deficient Plants by Triggering Jasmonic Acid Biosynthesis. - Herde, O. (1996)
To test whether the response to electrical current and heat treatment is due to the same signaling pathway that mediates mechanical wounding, we analyzed the effect of electric-current application and localized burning on proteinase inhibitor II (Pin2) gene expression in both wild-type and abscisic acid (ABA)-deficient tomato (Lycopersicon esculentum Mill.) and potato (Solanum phureja) plants. Electric-current application and localized burning led to the accumulation of Pin2 mRNA in potato and tomato wild-type plants. Among the treatments tested, only localized burning of the leaves led to an accumulation of Pin2 mRNA in the ABA-deficient plants. Electric-current application, like mechanical injury, was able to initiate ABA and jasmonic acid (JA) accumulation in wild-type but not in ABA-deficient plants. In contrast, heat treatment led to an accumulation of JA in both wild-type and ABA-deficient plants. Inhibition of JA biosynthesis by aspirin blocked the heat-induced Pin2 gene expression in tomato wild-type leaves. These results suggest that electric current, similar to mechanical wounding, requires the presence of ABA to induce Pin2 gene expression. Conversely, burning of the leaves activates Pin2 gene expression by directly triggering the biosynthesis of JA by an alternative pathway that is independent of endogenous ABA levels.